Distribusi dan Populasi Burung Manguni (Otus manadensis) di Gunung Kosibak, Taman Nasional Bogani Nani Wartabone - Fransisca Solang; Johny S. Tasirin; Wawan Nurmawan (COCOS, 2016)
ABSTRACTThe national park has an important role in the preservation of biodiversity, became the house for animals to living wildly. Otus manadensis is one of wild animals in the Bogani Nani Wartabone National Park is endemic species Sulawesi who have ecological role as pest controller. Quantitatively the spread of this species is not known for certain. This research conducted approximately 3 months from September – December 2015. Used methods of the point count and transect line. The point of observation is systematically divided into 4 segments based on the height of the surface of the sea. Three segments including in the national park area that is located in the Mount Kosibak while other segments is a production area or field located near the settlement. Research results obtained that Otus manadensis prefer areas with a good vegetation cover. There is a very high correlation between the condition of the vegetation cover with the density of Otus manadensis in Mount Kosibak. Otus manadensis density higher on the vegetation with basal area and importance value index is high.Key word : Population, Otus manadensis, Vegetation, Segment, Mount Kosibak, TNBNW